Peran Komite Audit dalam Memoderasi Kecurangan Laporan Keuangan pada Perusahaan Publik di Indonesia - Masthura; Nadirsyah; Mirna Indriani (Universitas Swadaya Gunung Jati, 2025)
This research aims to investigate the impact of financial stability, personal financial needs, and auditor turnover on financial statement fraud measured using the F-Score Model, while considering the role of the audit committee in preventing financial statement fraud. The research employs a causal approach with hypothesis testing. Secondary data are used, so the population in this study consists of manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2022. Purposive sampling method is employed, resulting in 63 companies with 252 units of analysis, namely financial statements. The results indicate that financial stability, personal financial needs, and auditor turnover significantly affect financial statement fraud. Meanwhile, the audit committee is able to moderate the relationship between financial stability, personal financial needs, and auditor turnover on financial statement fraud. These outcomes have crucial implications for understanding the dynamics of financial statement fraud and directing prevention and handling efforts more effectively in the future.